Differences in Corneal Parameters Between Affected and Normal Contralateral Eyes in Patients With Hemifacial Spasm Treated With Botulinum Toxin-A: Outcomes During One Complete Treatment Cycle. Issue 2 (February 2016) - Osaki, Teissy; Osaki, Midori H.; Osaki, Tammy H.; Hirai, Flavio E.; Campos, Mauro
Abstract : Purpose: To investigate possible temporary differences in corneal topographic parameters between affected and normal eyes in patients with hemifacial spasm (HFS) treated with botulinum toxin-A (BTX-A), over the course of 1 treatment cycle. Methods: This prospective study evaluated corneal topographic differences between affected and normal contralateral eyes during a 4-month period in patients with HFS treated with BTX-A (the duration of action of BTX-A for HFS ranges from 2 to 4 months). Corneal topographic analysis was performed using a conventional topographer (Atlas; Carl Zeiss Meditec, Dublin, CA). Steep K and astigmatism measurements were evaluated before BTX-A application and after 15 days and 2, 3, and 4 months. Results: Twenty-four patients (16 women and 8 men) were evaluated. Steep K [46.9 ± 3.6 diopters (D)] and astigmatism values (2.6 ± 2.5 D) were significantly higher in affected eyes of HFS patients than in nonaffected eyes (45.0 ± 1.4 D and 0.9 ± 0.6 D) before treatment ( P = 0.001 for steep K and P = 0.0003 for astigmatism). Astigmatism values also showed significant differences between the affected eye (1.4 ± 0.8 D) and nonaffected eye (0.9 ± 0.6 D) at 4 months ( P = 0.006), whereas steep K showed significant differences between both eyes at 15 days (affected eye: 45.6 ± 1.5 D, nonaffected eye: 45.0 ± 1.4 D, P = 0.008), 3 months (affected eye: 45.6 ± 1.8 D, nonaffected eye: 45.1 ± 1.3 D, P = 0.03) and 4 months (affected eye: 45.8 ± 1.2 D, nonaffected eye: 45.1 ± 1.4 D, P = 0.003) after treatment. Conclusions: The differences in steep K, and especially in astigmatism values, between eyes tended to reduce during the period of action of BTX-A. At 4 months, when the BTX-A effect is considered to be over or very reduced, a significant difference between eyes for both parameters was noted again.